2016
DOI: 10.4103/1658-354x.169482
|View full text |Cite
|
Sign up to set email alerts
|

Role of intraseptal anesthesia for pain-free dental treatment

Abstract: Pain control during the dental procedure is essentials and challenging. A complete efficacious pulp anesthesia has not been attained yet. The regional anesthesia such as inferior alveolar nerve block (IANB) only does not guarantee the effective anesthesia with patients suffering from irreversible pulpitis. This main aim of this review was to discuss various aspects of intraseptal dental anesthesia and its role significance in pain-free treatment in the dental office. In addition, reasons of failure and limitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 44 publications
(65 reference statements)
0
20
0
Order By: Relevance
“…Building-up pressure arising from the deposition of LA solution under sticky gingiva will generate painful sensations in addition to the pain coming from the insertion of the needle. [ 1 ] So, the pain associated with such an anesthetic technique is coming from the perforation of the periosteum and the speed of the pressure of the fast injection. [ 1 30 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Building-up pressure arising from the deposition of LA solution under sticky gingiva will generate painful sensations in addition to the pain coming from the insertion of the needle. [ 1 ] So, the pain associated with such an anesthetic technique is coming from the perforation of the periosteum and the speed of the pressure of the fast injection. [ 1 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] So, the pain associated with such an anesthetic technique is coming from the perforation of the periosteum and the speed of the pressure of the fast injection. [ 1 30 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[41516] On the other hand, this study revealed that articaine has slightly faster onset time than mepivacaine. Although the tissue diffusion characteristics of articaine are not well-understood,[1] there is one possible account for the superiority of articaine over mepivacaine in terms of onset time of action. The great lipid solubility of articaine in additional to its high concentration formula as a 4% solution could be the reason for increasing the number of uncharged local anesthetic molecules crossing the nerve membrane.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] The dental practitioners' point of view about the optimal local anesthetic for use in dentistry is the fastest in action and least toxic. [ 5 6 7 8 ] Choosing the best local anesthetic agents regarding safety and speed of action is still unapproachable. [ 2 3 4 5 6 ] Most of the local anesthetic agents are producing vasodilation in particular amide group.…”
Section: Introductionmentioning
confidence: 99%